THE MOM INTRAPRENEURIAL PATH TO WORK-LIFE BALANCE: EXAMINING THE ROLE OF SALARY AS A MEDIATOR - Mambu, Bellatrix Kezia Debora; Suade, Yuyun Karystin Meilissa; Pagiling, Novieanty (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study examines how mom-intrapreneurship influences work–life balance among employed women in Indonesia, with salary tested as a mediating variable. Using a quantitative approach and Partial Least Squares Path Modeling (PLS-PM), the research assesses direct and indirect relationships among the constructs. The findings show four key results. First, mom-intrapreneurship positively affectssalary, indicating that women’s creativity, initiative, and involvement in intrapreneurial activities contribute to higher income. Second, mom-intrapreneurship also improves work–life balance, suggesting that the autonomy and flexibility gained through intrapreneurial roles help women better manage professional and domestic responsibilities. Third, salary does not significantly influence work–life balance, implying that increased earnings alone do not ensure greater harmony between work and personal life. Fourth, salary does not mediate the link between mom-intrapreneurship and work–life balance, highlighting that psychological and motivational factors—rather than financial ones—play a more important role in achieving life balance. Overall, the study concludes that the well-being of working mom is shaped more by intrinsic values derived from intrapreneurial engagement, such as autonomy, meaningful work, andrecognition, than by financial compensation. These insights contribute to gender-based intrapreneurship literature and offer practical guidance for organizations promoting flexibility, innovation, and sustainable employee well-being.